The isotopic composition of oxygen and carbon of the recent sediment from the Bled Lake and of the Pleistocene lacustrine chalk from the Julian Alps - Dolenec, Tadej; Pezdič, Jože; Ogorelec, Bojan; Mišič, Miha (Geologija, 1984)
The isotopic composition of oxygen and carbon in the recent sediment from the SW part of the Bled Lake indicates a Chemical precipitate, the so-called lacustrine chalk, which was formed mostly by precipitation of calcite in isotopic equilibrium with oxygen from the lake water at temperatures between about 5 and 18 °C. An entirely different isotopic composition of oxygen and carbon is typical for the lake chalk from some deposits in Slovenia. The latter is most probably of detrital origin, and its isotopic composition of both Chemical elements is the same as that of rocks which furnished the material for its formation.